Perlindungan Hukum terhadap Korban Bullying dalam Perspektif Viktimologi - Maria Cicilia Tri Palupi (MLJ Merdeka Law Journal, 2020)
Bullying is still not getting enough attention. In Indonesia, victims of bullying are not recognized by the perpetrators. Victims of bullying can only be silent, resigned, and cannot fight back. Protection of victims of bullying is still very minimal. This type of research is normative juridical research. This study uses a juridical-normative research approach, a statutory approach, and a victimological juridical approach. Legal materials use primary, secondary, and tertiary legal materials. Interpretation in research uses the historical interpretation of the provisions of law and systematic interpretation. The results showed that Victimology identified the rights of the victims. This view is very important considering that bullying itself is not considered a problem, but is considered a normal act in childhood. From this point of view, of course, the rights of victims of bullying have not been realized much, even though the impact of this behavior is very real. UU Number 31 of 2014 concerning Protection of Witnesses and Victims cannot be applied effectively to deal with victims and assist victims if there is a legal process that occurs because the Witness and Victim Protection Agency are only in the Central, not yet in the regions. So that the protection of witnesses and victims is only carried out by the relevant agencies and the policeAbstraksBullying masih kurang mendapat perhatian. Di Indonesia korban bullying tidak disadari oleh pelaku. Korban bullying hanya bisa diam, pasrah dan tidak bisa melawan. Perlindungan korban bullying masih sangat minim. Jenis penelitian ini adalah penelitian yuridis normatif. Penelitian ini menggunakan pendekatan penelitian yuridis-normatif, pendekatan undang-undang, dan pendekatan yuridis viktimologis. Bahan hukum menggunakan bahan hukum primer, sekunder, dan tersier. Interpretasi dalam penelitian menggunakan interpretasi historis dari ketentuan sebuah hukum dan interpretasi sistematis. Hasil penelitian menunjukkan Victimology mengidentifikasi hak-hak korban. Pandangan ini sangat penting mengingat bullying itu sendiri tidak dianggap sebagai masalah, tetapi dianggap sebagai tindakan yang wajar di masa kanak-kanak. Dari sudut pandang ini, tentunya hak-hak korban bullying belum banyak direalisasikan, padahal dampak dari perilaku tersebut sangat nyata. UU Nomor 31 Tahun 2014 tentang Perlindungan Saksi dan Korban tidak dapat diterapkan secara efektif untuk menangani korban dan mendampingi korban apabila ada proses hukum yang terjadi karena Lembaga Perlindungan Saksi dan Korban hanya ada di Pusat, belum di daerah. Sehingga perlindungan saksi dan korban hanya dilakukan oleh instansi terkait dan kepolisianDOI: https://doi.org/10.26905/mlj.v1i2.5494